The experience of secrecy. [article]. - Chun, Jinseok S.; Mason, Malia F.
The concept of secrecy calls to mind a dyadic interaction: one person hiding a secret from another during a conversation or social interaction. The current work, however, demonstrates that this aspect of secrecy is rather rare. Taking a broader view of secrecy as the intent to conceal information, which only sometimes necessitates concealment, yields a new psychology of secrecy. Ten studies demonstrate the secrets people have, what it is like to have a secret, and what about secrecy is related to lower well-being. We demonstrate that people catch themselves spontaneously thinking about their secrets?they mind-wander to them?far more frequently than they encounter social situations that require active concealment of those secrets. Moreover, independent of concealment frequency, the frequency of mind-wandering to secrets predicts lower well-being (whereas the converse was not the case). We explore the diversity of secrets people have and the harmful effects of spontaneously thinking about those secrets in both recall tasks and in longitudinal designs, analyzing more than 13,000 secrets across our participant samples, with outcomes for relationship satisfaction, authenticity, well-being, and physical health. These results demonstrate that secrecy can be studied by having people think about their secrets, and have implications for designing interventions to help people cope with secrecy. -- (from the authors)